2020
DOI: 10.1002/ecy.3130
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic compounds from leaf litter decomposition alter soil microbial communities and carbon dynamics

Abstract: Investigations into the transfer of carbon from plant litter to underlying soil horizons have primarily focused on the leaching of soluble carbon from litter belowground or the mixing of litter directly into soil. However, previous work has largely ignored the role of volatile organic compounds (VOCs) released during litter decomposition. Unlike most leaf carbon, these litter-derived VOCs are able to diffuse directly into the soil matrix. Here, we used a 99-d microcosm experiment to track VOCs produced during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Root VOCs can act as both signaling molecules and nutrient sources for soil microbes [68], and hence might influence the assembly and proliferation of root-associated microbiome. A microcosm experiment showed that VOC-derived carbon released (in the headspace) during decomposition of 13 C-labelled leaf litter accounted for fractions in microbial biomass (located separately from the decomposition site), suggesting that VOCs can be carbon sources for soil microbes [69]. In another study, gaseous ethylene produced by peanut roots (as a response to cyanide released by neighboring cassava plants) altered microbial composition of peanut rhizosphere by shifting the abundance of actinobacterial species, resulting in improved seed production [60].…”
Section: Chemistry Of "Volatile Affairs" On Plant Rootsmentioning
confidence: 99%
“…Root VOCs can act as both signaling molecules and nutrient sources for soil microbes [68], and hence might influence the assembly and proliferation of root-associated microbiome. A microcosm experiment showed that VOC-derived carbon released (in the headspace) during decomposition of 13 C-labelled leaf litter accounted for fractions in microbial biomass (located separately from the decomposition site), suggesting that VOCs can be carbon sources for soil microbes [69]. In another study, gaseous ethylene produced by peanut roots (as a response to cyanide released by neighboring cassava plants) altered microbial composition of peanut rhizosphere by shifting the abundance of actinobacterial species, resulting in improved seed production [60].…”
Section: Chemistry Of "Volatile Affairs" On Plant Rootsmentioning
confidence: 99%
“…CC BY 4.0 License. dynamics (McBride et al, 2020). However, it should be noted that this is not the only process linking deciduous litter and soil biota.…”
Section: Discussionmentioning
confidence: 99%
“…Like LMW-DOC, VOCs, including methanol and monoterpenes, function as microbial C substrates (Madyastha et al, 1977;Radajewski et al, 2002. ), drive microbial activity (Asensio et al, 2012;McBride et al, 2019), alter N transformations (Paavolainen et al, 1998;McBride et al, 2019), and alter microbial community composition (McBride et al, 2020). VOCs can enter the soil through a variety of mechanisms including root emission, organic matter decomposition, and soil-atmosphere exchange, (Asensio et al, 2007;Leff and Fierer, 2008;Wenke et al, 2010;Peñuelas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%